Effect of Transition Metal Addition in the Bioactivity of Borate Bioglass Dental Materials - Kamal, H.; Abdelghany, A.M. (The Journal of Dentists, 2015)
Objectives: The basic structure and some physical properties of a bioactive borate glasses doped with transition metals were prepared and investigated with the same molar composition as 45S5 glass but with all the silicon dioxide (SiO2) replaced by boron trioxide (B2O3). Methods: The biodegradability was explored and estimated by soaking the samples into simulated body fluid (SBF) at 37ºC for 30 days. The pH changes of solution were measured during the soaking periods in order to explore the ionic change processes. The structural changes in the crystalline phases obtained in the glass matrix before and after immersion in SBF were recognized by means of X-ray diffraction (XRD) and Fourier transform infrared analysis (FTIR). The surface modification was explored by means of scanning electron microscope (SEM). Results: All obtained results support the aggregation and formation of hydroxyapatite (Hap) layer with different amounts that depend on the type of transition metal added to the glass matrix. Conclusions: The biodegradation data and spectral analysis of different samples may consider the material to be a good candidate for use as dental biomaterials.